Sistem Informasi Personalia PT. Green Flexible Industries - B. Herawan Hayadi; Bayu Kusuma; Adyanata Lubis (RJOCS (Riau Journal of Computer Science), 2016)
Personnel Information System development in organizations or institutions institutions currently very rapidly with the number of publications and test the application of some researchers at universities around the world, Problems of Information Systems always be obstacles and barriers in the development of every organization. Identify the problem that there can be improvements in the development of Personnel Information System. The system is expected to provide facilities and improve work effectiveness and can produce a fast and accurate information. The method used to analyze the system, data processing and system design, information system can cope with delays in the process of computer-based data input.can collect data - the data from the Personnel Employee and Payroll into a single entity in the database, so it can be processed and presented into a useful information for the company